Kajian Ikonografi dan Fungsi Arca Hindu-Buddha di Pura Agung Batan Bingin Pejeng Kawan - Raka Dewantara, Anak Agung Gede; Srijaya, I Wayan; Sapta Jaya, Ida Bagus (Humanis; Vol 24 No 3 (2020)DO - 10.24843/JH.2020.v24.i03.p05, 2020)
Period Hindu-Buddha in Indonesian, Leaving behind a variety of archaeological heights. Research to investigate the definition statue Hindu-Buddha at Agung Batan Bingin Temple, Pejeng Kawan Village. The purpose of this study is to reconstruct the history of Balinese culture in the past especially its aspect of religment. The writer apply this method for accumulation file like library study, observasion, interview as well as analysis, iconography. The theory used to help analysis is the functional theory. Based on the results of the research Found that there is an iconography mark in the statues of Hindu-Buddha on Agung Batan Bingin Temple. Iconography mark show the variety of jewelry, clothing, art, and posture depiction. Statue Hindu-Buddha on Bingin Temple including to ancient Balinese periodic. Statue Hindu-Buddha on Agung Batan Bingin Temple untill now still being used as an instrument of veneration by the people of Bali performing religious ceremonies, the Balinese people used to call it "Penyungsung Pura". Statue Hindu-Buddha the, believed in society pejeng kawan village as a means of begging for protection, safety, and plants fertility in society Pejeng Kawan Village.